Resin composition for forming magnetic core and structure
The resin composition for magnetic cores, optimized through transfer molding with controlled gelation time, addresses moldability and magnetic property issues, resulting in high-strength, uniformly distributed magnetic cores suitable for large structures.
Patent Information
- Application Number
- JP2023110084
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-10-20
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2038-10-19
AI Technical Summary
Existing methods for forming magnetic cores using potting materials face challenges in moldability and magnetic properties due to issues with viscosity control, sedimentation of magnetic powder, and uneven distribution, which affect the formability and magnetic properties of the cores.
A resin composition for forming magnetic cores containing highly filled magnetic powder is developed, utilizing transfer molding with a gelation time between 5 seconds and 300 seconds at 175°C, which improves moldability and magnetic properties by ensuring uniform distribution of the magnetic powder.
The resin composition achieves improved moldability and magnetic properties, enabling the production of magnetic cores with high mechanical strength and consistent magnetic performance, suitable for large structures such as in-vehicle reactors.
Smart Images

Figure 0007609205000006 
Figure 0007609205000001 
Figure 0007609205000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for forming a magnetic core and a structure. [Background technology]
[0002] Various methods have been developed so far as a technique for forming a magnetic core in a reactor. For example, the technique described in Patent Document 1 is known as this type of technique. Patent Document 1 describes that a reactor in which a coil, a magnetic core (inner core Mi), and an exterior member (outer core Mo) that houses them are integrated can be obtained by placing a coil in a mold, and then casting and curing a mixed material of soft magnetic powder and resin as a potting material (paragraph 0071, FIG. 3 of Patent Document 1). The same document also describes that the magnetic core is obtained by casting and curing a potting material under atmospheric pressure or a predetermined low pressure (paragraph 0045 of Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-75596 A Summary of the Invention [Problem to be solved by the invention]
[0004] As a result of the inventors' investigations, it was found that the magnetic core made of the potting material described in Patent Document 1 has room for improvement in terms of moldability and magnetic properties. [Means for solving the problem]
[0005] The above-mentioned Patent Document 1 describes that when using a potting material, it is necessary to ensure the pot life by suppressing an increase in viscosity during the process from mixing to injection into a mold. The above-mentioned Patent Document 1 describes that when using a potting material, it is necessary to ensure the pot life by suppressing the increase in viscosity during the process from mixing to injection into a mold. In such casting techniques, it is known that the potting material is designed to have a long gelling time (usually 10 minutes or more) in consideration of the pot life, degassing process, etc. Also, when the magnetic powder is highly packed, it becomes solid rather than paste-like, and there is a risk that it cannot be used as a potting material.
[0006] Therefore, the inventors conducted further research and found that by adopting transfer molding, it is possible to highly pack the magnetic powder in the resin composition for forming the magnetic core (resin composition for forming the magnetic core), thereby improving the mechanical strength and magnetic properties. However, it has been found that if the gelation time during transfer molding is too long, although the detailed mechanism is unclear, settling of the magnetic powder occurs, and the density of the magnetic powder becomes non-uniform (uneven distribution occurs), resulting in a deterioration of the magnetic properties. On the other hand, if the gelation time during transfer molding is too short, the distance the molding material must travel becomes shorter, which imposes restrictions on the molding size, although the detailed mechanism is unclear. As a result, it is thought that unfilled portions occur during the molding process of large structures such as reactors (magnetic cores), resulting in reduced moldability. Based on this knowledge, further intensive research led to the discovery that in a resin composition for forming a magnetic core containing a high loading of magnetic powder, the moldability and magnetic properties of the resin composition can be improved by setting the gelation time at the molding temperature within a predetermined range, and thus completed the present invention.
[0007] According to the present invention, A resin composition for forming a magnetic core for forming a magnetic core filled inside an air-core coil, comprising: A thermosetting resin; A magnetic powder; The content of the magnetic powder is 50% by mass or more based on the total solid content of the resin composition for forming a magnetic core, The resin composition for forming a magnetic core has a gel time at 175° C. of 5 seconds or more and 300 seconds or less.
[0008] According to the present invention, there is also provided a structure including a magnetic core made of a cured product of the above-mentioned resin composition for forming a magnetic core. Effect of the Invention
[0009] According to the present invention, there are provided a resin composition for forming a magnetic core, which has excellent moldability and magnetic properties, and a structure using the same. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view showing a configuration of a structure according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, the same components are given the same reference numerals, and the description will be omitted as appropriate. In addition, the drawings are schematic diagrams, and do not correspond to the actual dimensional ratio.
[0012] The resin composition for forming a magnetic core of the present embodiment is a resin composition for forming a magnetic core filled inside an air-core coil. A cured product of the resin composition for forming a magnetic core can be used as a magnetic core (magnetic element) such as a dust core.
[0013] The magnetic core forming resin composition of the present embodiment may contain a thermosetting resin and a magnetic powder. The content of the magnetic powder may be 50% by mass or more based on the total solid content of the magnetic core forming resin composition. The gel time of the magnetic core forming resin composition at 175°C may be 5 seconds or more and 300 seconds or less.
[0014] The present inventors have focused on magnetic properties such as high magnetic permeability and low magnetic loss, and mechanical properties, and have conducted in-depth research into a method for highly filling a magnetic powder as a metal filler in a resin composition for forming a magnetic core. As a result, they have found that the filling rate of the magnetic powder in the resin composition for forming a magnetic core (for example, 50% by mass or more of the total solid content of the resin composition for forming a magnetic core) can be increased by adopting transfer molding using a thermosetting resin. Since a magnetic core highly filled with magnetic powder can be realized, it is possible to improve the mechanical strength of the magnetic core. It is also expected that the magnetic properties of the magnetic core can be improved. According to the findings of the present inventors, it has been found that by setting the gelation time at the molding temperature of transfer molding to the above-mentioned lower limit or more, it is possible to improve the moldability of coils (large structures) such as reactors for vehicles. It has also been found that by setting the gelation time at the molding temperature of transfer molding to the above-mentioned upper limit or less, it is possible to suppress uneven distribution of the magnetic powder during molding, although the detailed mechanism is unclear, and therefore it is possible to suppress the occurrence of variations in the relative magnetic permeability and improve the magnetic properties.
[0015] The structure having a magnetic core made of the cured product of the resin composition for forming a magnetic core of the present embodiment can be used for various inductor applications, and can be used as a reactor as an example. According to the present embodiment, a converter having a reactor and a power conversion device having this converter can be provided. The inductor can be used for vehicles, aircraft, ships, etc.
[0016] Each component of the resin composition for forming a magnetic core of this embodiment will be described in detail below.
[0017] The resin composition for forming a magnetic core of this embodiment (hereinafter, may be simply referred to as a resin composition) can contain a thermosetting resin and a magnetic powder.
[0018] <Thermosetting resin> Examples of the thermosetting resin include epoxy resin, phenol resin, polyimide resin, bismaleimide resin, urea resin, melamine resin, polyurethane resin, cyanate ester resin, silicone resin, oxetane resin (oxetane compound), (meth)acrylate resin, unsaturated polyester resin, diallyl phthalate resin, benzoxazine resin, etc. These may be used alone or in combination of two or more.
[0019] Specific examples of the thermosetting resin include novolac-type phenolic resins such as phenol novolac resin, cresol novolac resin, bisphenol A-type novolac resin, and triazine skeleton-containing phenol novolac resin; phenolic resins such as unmodified resol phenolic resin, oil-modified resol phenolic resin modified with tung oil, linseed oil, and walnut oil, and aralkyl-type phenolic resins such as phenol aralkyl resin and biphenyl aralkyl-type phenolic resin; bisphenol type epoxy resins such as bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, tetramethyl bisphenol F-type epoxy resin, bisphenol S-type epoxy resin, bisphenol E-type epoxy resin, bisphenol M-type epoxy resin, bisphenol P-type epoxy resin, and bisphenol Z-type epoxy resin; and novolacs such as phenol novolac-type epoxy resin and cresol novolac-type epoxy resin. epoxy resins such as biphenyl type epoxy resins, biphenyl aralkyl type epoxy resins, aryl alkylene type epoxy resins, naphthalene type epoxy resins, anthracene type epoxy resins, phenoxy type epoxy resins, dicyclopentadiene type epoxy resins, norbornene type epoxy resins, adamantane type epoxy resins, fluorene type epoxy resins, and trisphenylmethane type epoxy resins; resins having a triazine ring such as urea resins and melamine resins; unsaturated polyester resins; maleimide resins such as bismaleimide compounds; polyurethane resins; diallyl phthalate resins; silicone-based resins; benzoxazine resins; polyimide resins; polyamide imide resins; cyanate ester resins such as benzocyclobutene resins, novolac type cyanate resins, bisphenol A type cyanate resins, bisphenol E type cyanate resins, and tetramethyl bisphenol F type cyanate resins. The thermosetting resin may be one of these alone, or two or more types having different weight average molecular weights may be used in combination, or one or more types may be used in combination with their prepolymers. The thermosetting resin may be in a semi-cured (solid) state at room temperature of 25°C.
[0020] From the viewpoint of heat resistance, the thermosetting resin may contain, for example, an epoxy resin. The epoxy resin may contain a polyfunctional epoxy resin having two or more epoxy groups in the molecule. As the epoxy resin, for example, one or more solid epoxy resins selected from the group consisting of trisphenylmethane type epoxy resins, dicyclopentadiene type epoxy resins, bisphenol A type epoxy resins, and tetramethylbisphenol F type epoxy resins may be used. This provides a resin composition that is highly heat resistant and suitable for molding.
[0021] The content of the thermosetting resin in this embodiment is, for example, 5% by volume to 50% by volume, and preferably 10% by volume to 40% by volume, based on 100% by volume of the total solid content of the resin composition. The content of the thermosetting resin in this embodiment is, for example, 0.5% by mass to 20% by mass, and preferably 1% by mass to 15% by mass, based on 100% by mass of the total solid content of the resin composition. By setting the content in such a numerical range, it is possible to improve moldability and mechanical properties.
[0022] In this embodiment, the "solid content of the resin composition" refers to the non-volatile content in the resin composition, and refers to the remainder excluding volatile components such as water and solvent. When a solvent is included, the content relative to the entire resin composition refers to the content relative to the entire solid content of the resin composition excluding the solvent. In addition, unless otherwise specified, "~" indicates that the upper and lower limits are included.
[0023] The resin composition of the present embodiment may contain a curing agent for the thermosetting resin. The curing agent may be in a semi-cured (solid) state at room temperature (25° C.).
[0024] When the thermosetting resin contains a phenolic resin such as a novolac type phenolic resin, for example, hexamethylenetetramine can be used as the curing agent. Furthermore, when the thermosetting resin contains an epoxy resin, examples of the curing agent that can be used include amine compounds such as aliphatic polyamines, aromatic polyamines, aromatic diamines, and diamine diamide; acid anhydrides such as alicyclic acid anhydrides and aromatic acid anhydrides; polyphenol compounds (phenol-based curing agents) such as novolac-type phenolic resins; and imidazole compounds. Furthermore, when the thermosetting resin contains a maleimide resin, for example, an imidazole compound can be used as the curing agent. These may be used alone or in combination of two or more.
[0025] From the viewpoints of glass transition temperature and linear expansion coefficient, the curing agent may contain an aromatic diamine. The aromatic diamine can be any compound having one or more aromatic ring structures and two amino groups (-NH2) in one molecule. The aromatic diamine is preferably one having a structure in which the amino group is directly bonded to the aromatic ring.
[0026] When selecting an aromatic diamine, the melting point can be used as a reference. By using an aromatic diamine with an appropriate melting point, the aromatic diamine melts appropriately when kneading / molding the resin composition. This can improve the fluidity. In addition, since the resin composition can be kneaded more uniformly, it is thought that the heat resistance and mechanical properties (strength, etc.) of the finally obtained cured product (magnetic member) can be improved. Specifically, the melting point of the aromatic diamine is preferably 160° C. or lower, more preferably 150° C. or lower, and further preferably 140° C. or lower. There is no particular lower limit for the melting point of the aromatic diamine, but it is, for example, 60° C. or higher, preferably 70° C. or higher, and more preferably 80° C. or higher. When a commercially available aromatic diamine is used, the melting point may be determined according to the catalogue value.
[0027] Incidentally, it is preferable that the aromatic diamine is a solid, not a liquid, at room temperature (25° C.). The resin composition of the present embodiment may contain an amine compound other than the aromatic diamine, but it is preferable that the amine compound is also a solid, not a liquid, at room temperature (25° C.). The resin composition of the present embodiment is typically prepared in the form of granules or tablets. From the viewpoint of ease of preparation and handling of the prepared granular or tablet-shaped resin composition, it is preferable that the aromatic diamine (and, in some cases, an amine compound other than the aromatic diamine) is a solid at room temperature.
[0028] The resin composition preferably contains a compound represented by the following general formula (AM) as an aromatic diamine.
[0029] [ka]
[0030] In general formula (AM), X, when a plurality of Xs are present, each independently represents any group selected from the group consisting of a single bond, a linear or branched alkylene group, an ether group, a carbonyl group, an ester group, and a group in which two or more of these groups are linked together; Y is any group selected from the group consisting of a single bond, a linear or branched alkylene group, an ether group, a carbonyl group, an ester group, and a group in which two or more of these groups are linked together; R 1 , R 2 and R 3 When a plurality of groups are present, each group is independently a monovalent organic group, a hydroxyl group, or a halogen atom, k, l and m each independently represent an integer of 0 to 4; n is an integer equal to or greater than 0.
[0031] The linear or branched alkylene group of X and Y preferably has 1 to 6 carbon atoms, and more preferably has 1 to 3 carbon atoms. In addition, by making part or all of X and Y branched alkylene groups, the skeleton of the aromatic diamine can be made moderately rigid. This is thought to be related to the above-mentioned "melting point" being appropriate. In addition, by making the skeleton of the aromatic diamine moderately rigid, it is thought that the effect of further improving the heat resistance and mechanical strength of the cured product (magnetic member) can be obtained.
[0032] R 1 , R 2 and R 3 Examples of the monovalent organic group include an alkyl group, an alkenyl group, an alkynyl group, an alkylidene group, an aryl group, an aralkyl group, an alkaryl group, a cycloalkyl group, an alkoxy group, a heterocyclic group, and a carboxyl group. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a neopentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, and a decyl group. Examples of the alkenyl group include an allyl group, a pentenyl group, and a vinyl group. The alkynyl group includes, for example, an ethynyl group. Examples of the alkylidene group include a methylidene group and an ethylidene group. Examples of the aryl group include a tolyl group, a xylyl group, a phenyl group, a naphthyl group, and an anthracenyl group. Examples of the aralkyl group include a benzyl group and a phenethyl group. Examples of the alkaryl group include a tolyl group and a xylyl group. Examples of the cycloalkyl group include an adamantyl group, a cyclopentyl group, a cyclohexyl group, and a cyclooctyl group. Examples of the alkoxy group include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, an s-butoxy group, an isobutoxy group, a t-butoxy group, an n-pentyloxy group, a neopentyloxy group, and an n-hexyloxy group. Examples of the heterocyclic group include an epoxy group and an oxetanyl group. R 1 , R 2 and R 3 The total number of carbon atoms in each of the monovalent organic groups is, for example, 1 to 30, preferably 1 to 20, more preferably 1 to 10, and particularly preferably 1 to 6.
[0033] k, l and m are each independently an integer of preferably 0 or 1. In one embodiment, k, l and m are all 0. That is, in one embodiment, all of the benzene rings in general formula (AM) are not substituted with atomic groups other than amino groups. n is preferably 0 to 3, and more preferably 0 to 2.
[0034] Specific examples of aromatic diamines are shown below. However, the aromatic diamines are not limited to the following. Other examples include 1,3-bis[1-(4-aminophenyl)-1-methylethyl]benzene, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, and 1,3-bis(4-aminophenoxy)benzene.
[0035] [ka]
[0036] The aromatic diamine may be a commercially available product, and may be obtained, for example, from Seika Corporation, Mitsui Fine Chemicals, Inc., Fujifilm Wako Pure Chemical Industries, Ltd., or the like.
[0037] The resin composition of the present embodiment may contain only one type of aromatic diamine, or may contain two or more types of aromatic diamine. The amount of the aromatic diamine in the resin composition is, for example, 0.1 to 20 mass %, and preferably 0.5 to 10 mass %, based on the total mass of the resin composition. The amount of aromatic diamine in the resin composition is, for example, 1 to 30% by volume, preferably 5 to 25% by volume, based on the entire resin composition. By setting the amount in such a range, moldability and mechanical properties can be improved.
[0038] The amount of the aromatic diamine in the composition is preferably appropriately adjusted in relation to the epoxy resin. Specifically, the ratio of the number of moles of epoxy groups in the epoxy resin to the number of moles of amino groups in the aromatic diamine (i.e., the number of moles of epoxy groups in the epoxy resin / the number of moles of amino groups in the aromatic diamine) is preferably 1 to 3, more preferably 1.5 to 2.5, and even more preferably 1.7 to 2.3. One amino group (-NH2) can react with two epoxy groups. Therefore, by adjusting the ratio of the epoxy resin and aromatic diamine so that the above ratio is around 2, it is believed that the crosslinked structure between the amino group and the epoxy group during curing can be made denser. It is also believed that the glass transition temperature of the cured product (magnetic member) can be increased, and the heat resistance can be improved. The above ratio can be determined by calculation from the epoxy equivalent or epoxy value of the epoxy resin contained in the composition, the molecular weight of the epoxy resin (which is usually shown in a catalog for the epoxy resin), the molecular weight of the aromatic diamine, and the like.
[0039] The content of the curing agent in this embodiment is, for example, 5% by volume to 30% by volume, and preferably 5% by volume to 25% by volume, based on 100% by volume of the total solid content of the resin composition. The content of the curing agent in this embodiment is, for example, 0.5% by mass to 20% by mass, and preferably 1% by mass to 15% by mass, based on 100% by mass of the total solid content of the resin composition. By setting the content in such a numerical range, it is possible to improve moldability and mechanical properties.
[0040] The resin composition of the present embodiment may contain a thermoplastic resin, which can further improve the moldability of the resin composition.
[0041] Examples of the thermoplastic resin include acrylic resin, polyamide resin (e.g., nylon, etc.), thermoplastic urethane resin, polyolefin resin (e.g., polyethylene, polypropylene, etc.), polycarbonate, polyester resin (e.g., polyethylene terephthalate, polybutylene terephthalate, etc.), polyacetal, polyphenylene sulfide, polyether ether ketone, liquid crystal polymer, fluororesin (e.g., polytetrafluoroethylene, polyvinylidene fluoride, etc.), modified polyphenylene ether, polysulfone, polyether sulfone, polyarylate, polyamide imide, polyether imide, thermoplastic polyimide, etc. In addition, the thermoplastic resin may be used alone, or two or more types having different weight average molecular weights may be used in combination, or one or more types may be used in combination with their prepolymers.
[0042] <Magnetic powder> The resin composition of the present embodiment may contain magnetic powder. The magnetic powder may be composed of a mixed powder having iron-based particles and fine particles different from the iron-based particles.
[0043] The magnetic powder may contain two or more types of particles having different average particle sizes, which can enhance the filling ability of the magnetic powder and the flowability of the resin composition.
[0044] (Iron-based particles) The first particles contained in the iron-based particles can be soft magnetic particles having an iron content of 85 mass % or more (soft magnetic high iron content particles). The iron-based particles can include first particles and second particles. These can be used alone or in combination of two or more kinds.
[0045] Soft magnetism refers to ferromagnetism with a small coercive force, and generally, ferromagnetism with a coercive force of 800 A / m or less is called soft magnetism.
[0046] The material of the first particle may be a metal material having an iron content of 85% by mass or more as a constituent element. Such a metal material having a high iron content as a constituent element exhibits soft magnetism with relatively good magnetic properties such as magnetic permeability and magnetic flux density. Therefore, when molded into a magnetic core or the like, a resin composition that can exhibit good magnetic properties can be obtained.
[0047] In addition, the form of this metal material may be, for example, a simple substance, or an alloy such as a solid solution, a eutectic, or an intermetallic compound. By using the first particles made of such a metal material, it is possible to obtain a resin composition having excellent magnetic properties derived from iron, that is, magnetic properties such as high magnetic permeability and high magnetic flux density.
[0048] The metal material may contain elements other than iron as constituent elements, such as B, C, N, O, Al, Si, P, S, Ti, V, Cr, Mn, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Cd, In, and Sn, and one or more of these may be used in combination.
[0049] Specific examples of the metal material include pure iron, silicon steel, iron-cobalt alloy, iron-nickel alloy, iron-chromium alloy, iron-aluminum alloy, carbonyl iron, stainless steel, and composite materials containing one or more of these.
[0050] The average particle size of the iron-based particles is not particularly limited as long as it is more than 3 μm, but is preferably 4 to 180 μm, more preferably 5 to 150 μm, and even more preferably 7 to 100 μm. By having the average particle size of the iron-based particles within the above range, the fluidity of the resin composition can be further improved.
[0051] By setting the average particle size of the iron-based particles to the above lower limit or more, it is possible to prevent the moldability of the resin composition from being reduced due to the specific gravity, particle shape, etc. of the constituent material of the first particles. On the other hand, by setting the average particle size of the iron-based particles to the above upper limit or less, it is possible to prevent the iron-based particles from easily settling in the resin composition due to the specific gravity, particle shape, etc. of the constituent material of the first particles, which would result in reduced uniformity.
[0052] The average particle size of the first particles is not particularly limited, but is preferably 10 to 180 μm, more preferably 12 to 150 μm, and even more preferably 15 to 100 μm. When the average particle size of the first particles is within the above range, the moldability of the resin composition can be further improved.
[0053] The material constituting the first particles may be a crystalline material, an amorphous material, or a mixture of these materials in the particles.
[0054] Furthermore, the iron-based particles may be a mixture of first particles made of a crystalline material and first particles made of an amorphous material. This results in two types of first particles with different surface hardness being mixed together. As a result, the interaction between the first particles during flow is optimized, ensuring higher flowability.
[0055] The sphericity of the first particles is not particularly limited, but is preferably 0.60 to 1.00, and more preferably 0.70 to 1.00. When the sphericity of the first particles is within the above range, the flowability of the resin composition can be further improved.
[0056] The second particles contained in the iron-based particles can be particles (soft magnetic metal particles) that exhibit soft magnetism and have a different composition of constituent material from the first particles.
[0057] The constituent material of the second particles is appropriately selected from the materials described above as the constituent material of the first particles. The term "compositionally different" means that the content of the constituent elements differs by 1 mass % or more.
[0058] By using second particles with a different composition of constituent material from the first particles, two types of particles with different surface chemical states and surface hardness are mixed together, which optimizes the interaction between the first and second particles during flow and ensures higher flowability.
[0059] In addition, the average particle size of the second particles is not particularly limited, but is preferably different from the average particle size of the first particles. That is, the average particle size of the second particles may be larger than the average particle size of the first particles, but is preferably smaller. This makes it possible to suppress a decrease in the fluidity of the resin composition even if the resin composition contains first particles with a relatively large particle size. That is, while ensuring the excellent magnetic properties derived from the first particles, the second particles can also ensure high fluidity of the resin composition.
[0060] When the average particle size of the second particles is smaller than that of the first particles, the difference between the average particle size of the first particles and the average particle size of the second particles is appropriately set in consideration of the fluidity of the resin composition, and is preferably 1 to 100 μm, more preferably 3 to 80 μm, even more preferably 5 to 60 μm, and particularly preferably 10 to 50 μm, for example. This can further increase the fluidity of the resin composition.
[0061] By making the difference in average particle diameter equal to or greater than the lower limit, the effect of increasing fluidity can be achieved. In addition, the particle diameter difference between the first particles and the second particles becomes small, and the effect of the second particles being arranged to fill the gaps between the first particles becomes weak, thereby preventing a decrease in the filling ability of the magnetic material. On the other hand, by making the difference in average particle diameter equal to or less than the upper limit, the particle diameter of the second particles becomes too small due to the particle diameter of the first particles, thereby preventing a decrease in the fluidity of the resin composition.
[0062] The material constituting the second particles may be a crystalline material, an amorphous material, or a mixture of these materials.
[0063] The sphericity of the second particles is not particularly limited, but is preferably 0.60 to 1.00, and more preferably 0.70 to 1.00. When the sphericity of the second particles is within the above range, the flowability of the resin composition can be further improved.
[0064] The resin composition of the present embodiment may or may not contain second particles, as necessary.
[0065] The resin composition of the present embodiment may contain spherical particles. As the spherical particles, iron-based particles such as the first particles and the second particles having the above-mentioned sphericity may be used. This can improve the filling property of the magnetic powder and the flowability of the resin composition.
[0066] Furthermore, the magnetic powder may contain soft magnetic particles other than the first particles and the second particles, such as Ni-based soft magnetic particles, Co-based soft magnetic particles, and the like.
[0067] At least one of the iron-based particles, that is, the first particles and the second particles, may be subjected to a surface treatment.
[0068] In this embodiment, the surface treatment refers to an operation for modifying the particle surface. For example, the operation includes treating the particle surface with a coupling agent or treating the particle with plasma. By such surface treatment, it is possible to bond a functional group to the surface of the first particle and / or the second particle. The functional group can cover a part or the whole surface of these particle surfaces.
[0069] As such a functional group, a functional group of the following general formula (1) can be used. *-OXR···(1) [In the formula, R represents an organic group, X represents Si, Ti, Al, or Zr, and * represents one of the atoms constituting the first particle or the second particle.]
[0070] The functional group is a residue formed by surface treatment with a known coupling agent such as a silane coupling agent, a titanium coupling agent, an aluminum coupling agent, or a zirconium coupling agent, and is preferably a residue of a coupling agent selected from the group consisting of a silane coupling agent and a titanium coupling agent. This makes it possible to further increase the flowability of a resin composition when the magnetic powder is blended with the resin composition.
[0071] In addition, when bonding the functional groups as described above, plasma treatment may be performed in advance as part of the surface treatment of the first particles. For example, by performing oxygen plasma treatment, OH groups are generated on the surface of the first particles, which makes it easier for the first particles to bond with the residue of the coupling agent via oxygen atoms. This allows the functional groups to be bonded more firmly.
[0072] Incidentally, whether the first particle and the residue of the coupling agent are bonded via an oxygen atom in the first particle can be confirmed, for example, by using a Fourier transform infrared spectrophotometer.
[0073] Moreover, the above-mentioned surface treatment may be applied to the second particles, or may be applied to both the first particles and the second particles.
[0074] From the viewpoint of increasing the fluidity of the resin composition, the surface treatment may be performed only on the first particles. This makes the surface states of the first particles and the second particles different from each other, and therefore each particle behaves differently in interaction with the thermosetting resin, which can contribute to increasing the fluidity.
[0075] In addition, the base of the above-mentioned surface treatment may be subjected to another coating treatment. Examples of such coating treatment include a resin coating such as a silicone resin, a silica coating, etc. By applying such a coating treatment, the insulating properties of the iron-based particles can be further improved. Such a coating treatment may be applied as necessary, and may be omitted. This coating treatment may be applied alone, not as a base for the above-mentioned surface treatment.
[0076] The volume fraction of the iron-based particles is preferably 35% to 90% by volume, more preferably 40% to 85% by volume, based on 100% by volume of the total solid content of the resin composition, which provides a sufficiently high content of the iron-based particles, thereby providing a resin composition with good magnetic properties.
[0077] By setting the volume fraction of the iron-based particles to the lower limit or more, it is possible to prevent the magnetic properties of the resin composition from being deteriorated due to the magnetic properties of the iron-based particles, while by setting the volume fraction of the iron-based particles to the upper limit or less, it is possible to prevent the flowability of the resin composition from being deteriorated or the mechanical properties after curing from being deteriorated due to a relative decrease in the volume fraction of the thermosetting resin.
[0078] The mass fraction of the iron-based particles is preferably 55% to 97% by mass, more preferably 60% to 95% by mass, relative to 100% by mass of the total solid content of the resin composition, although this varies depending on the specific gravity of each component. This makes it possible to obtain a resin composition with good magnetic properties, as in the case of the volume fraction.
[0079] (microparticles) The resin composition of the present embodiment exhibits soft magnetism and can contain microparticles having a particle size of 3 μm or less.
[0080] The resin composition containing the above-mentioned fine particles exhibits high fluidity during molding, and the exudation of the thermosetting resin during molding is suppressed. Therefore, the moldability of the resin composition is improved, and the filling and uniformity of the magnetic powder can be further improved, so that the molded body can have good magnetic properties. In addition, the suppression of the exudation of the thermosetting resin suppresses the occurrence of resin burrs and the like during molding. In addition, it is possible to prevent the component balance of the resin composition from being lost due to the exudation of the thermosetting resin, which causes the mechanical properties of the molded body to deteriorate. Therefore, a molded body with few molding defects can be obtained.
[0081] The reason why the exudation of the thermosetting resin is suppressed is that the microparticles clog the exudation path of the thermosetting resin during molding, thereby blocking this path.
[0082] In addition, by including the fine particles, the volume fraction of the magnetic material in the resin composition can be increased. In other words, the fine particles can easily enter gaps, and therefore the filling property of the magnetic material can be increased accordingly. As a result, the magnetic properties of the resin composition can be further improved.
[0083] The constituent material of the microparticles may be appropriately selected from the materials mentioned above as the constituent material of the first particles, or may be other soft magnetic materials (such as soft ferrite, Ni-based soft magnetic material, Co-based soft magnetic material, etc.).
[0084] The composition of the constituent material of the microparticles may be the same as or different from the composition of the constituent materials of the first and second particles. The composition of the constituent materials is different when the content of the constituent elements differs by 1 mass % or more.
[0085] By using microparticles with a different composition of constituent material from the first and second particles in this way, particles with different surface chemical states and surface hardness are mixed in the resin composition, which optimizes the interaction between the iron-based particles and the microparticles during flow, ensuring higher flowability.
[0086] The particle size of the microparticles is not particularly limited as long as it is 3 μm or less, but it is preferable that the microparticles have a size of 0.1 to 2.8 μm. Such a particle size is necessary for the microparticles to fill the exudation path of the thermosetting resin, and is a particle size that allows the microparticles to easily flow together with the molten thermosetting resin.
[0087] The sphericity of the microparticles is not particularly limited, but is preferably 0.30 to 1.00, and more preferably 0.50 to 1.00. By making the sphericity of the microparticles within the above range, the flowability of the resin composition is ensured by utilizing the rolling of the microparticles themselves, while the microparticles tend to clog gaps and the like, making it easier to suppress the exudation of the thermosetting resin. In other words, it is possible to achieve both the flowability of the resin composition and the suppression of the exudation of the microparticles.
[0088] As described above, the resin composition only needs to contain fine particles having a particle diameter of 3 μm or less, and the content of the fine particles in the magnetic powder is defined as a relative ratio to the iron-based particles.
[0089] That is, the volume fraction of the fine particles is preferably 5 to 50 volume % of the iron-based particles, and more preferably 7 to 45 volume %. This optimizes the content of the fine particles, resulting in a resin composition that has sufficient fluidity and can more reliably suppress the exudation of the thermosetting resin.
[0090] If the volume fraction of the fine particles is below the lower limit, the effect of improving the flowability of the fine particles is reduced, and the flowability of the resin composition is reduced, and the effect of suppressing the exudation of the thermosetting resin is also reduced. If the volume fraction of the fine particles is above the upper limit, the volume fraction of the iron-based particles is relatively reduced, and the volume fraction of the thermosetting resin is relatively reduced, which may lead to a decrease in the magnetic properties and flowability of the resin composition.
[0091] An example of the mass fraction of the fine particles is preferably 5 to 35% by mass, more preferably 8 to 33% by mass, based on 100% by mass of the total solid content of the resin composition, although it varies depending on the specific gravity of each component. An example of the volume fraction of the fine particles is 5 to 30% by volume, more preferably 8 to 27% by volume, based on 100% by volume of the total solid content of the resin composition. This makes it possible to obtain a resin composition that has sufficient fluidity and can more reliably suppress the exudation of the thermosetting resin, similar to the case of the volume fraction.
[0092] The content of the magnetic powder containing the iron-based particles and microparticles is, for example, 80% by mass to 99.5% by mass, preferably 85% by mass to 98.5% by mass, and more preferably 90% by mass to 98.5% by mass, based on 100% by volume of the total solid content of the resin composition. The content of the magnetic powder containing the iron-based particles and microparticles is, for example, 40% by volume to 95% by volume, preferably 60% by volume to 90% by volume, based on 100% by volume of the total solid content of the resin composition. This makes it possible to realize a cured resin composition with excellent magnetic properties.
[0093] The content of the microparticles is, for example, 1% by mass to 40% by mass, preferably 35% by mass to 38% by mass, and more preferably 5% by mass to 35% by mass, based on 100% by mass of the entire magnetic powder including the iron-based particles and the microparticles. This optimizes the content of the microparticles, thereby obtaining a resin composition that has sufficient fluidity and can more reliably suppress the exudation of the thermosetting resin.
[0094] (Non-magnetic powder) The resin composition of the present embodiment may contain non-magnetic powder that exhibits non-magnetic properties.
[0095] The non-magnetic powder may be a powder that is non-magnetic and has an average particle size of 3 μm or less and is smaller than that of the iron-based particles. In this embodiment, non-magnetic means that it does not have ferromagnetic properties.
[0096] A resin composition containing such a non-magnetic powder exhibits higher fluidity during molding, and the exudation of the thermosetting resin during molding is further suppressed. This improves the moldability of the resin composition, and the filling and uniformity of the magnetic powder can be further improved, resulting in particularly good magnetic properties in the molded body. In addition, the suppression of the exudation of the thermosetting resin suppresses the occurrence of resin burrs and the like during molding. In addition, it is possible to prevent the mechanical properties of the molded body from deteriorating due to the component balance of the resin composition being lost due to the exudation of the thermosetting resin. Therefore, a molded body with few molding defects can be obtained.
[0097] The non-magnetic powder may be made of, for example, a ceramic material, a glass material, or the like, and a material containing at least one of these may be used. Among these, a material containing a ceramic material is preferably used. Such a non-magnetic powder has a high affinity with the thermosetting resin, and therefore can maintain the fluidity of the resin composition.
[0098] Examples of the ceramic material include oxide-based ceramic materials such as silica, alumina, zirconia, titania, magnesia, and calcia, nitride-based ceramic materials such as silicon nitride and aluminum nitride, and carbide-based ceramic materials such as silicon carbide and boron carbide, etc. Any one of these may be used alone, or a mixture containing any one of these may be used.
[0099] In particular, the ceramic material preferably contains silica, which has high affinity with thermosetting resins and high insulating properties, and is therefore useful as a constituent material of non-magnetic powders used in resin compositions.
[0100] The true specific gravity of the constituent material of the non-magnetic powder is preferably 1.0 to 6.0, more preferably 1.2 to 5.0, and even more preferably 1.5 to 4.5. Such non-magnetic powder has a small specific gravity and therefore easily flows together with the molten thermosetting resin. Therefore, when the molten thermosetting resin flows toward the gaps of the mold during molding, the non-magnetic powder easily flows together with the molten thermosetting resin. As a result, the gaps are blocked by the non-magnetic powder, and the exudation of the thermosetting resin can be more reliably suppressed. The gaps of the mold include, for example, the gaps (clearances) between the plunger and cylinder of a transfer molding machine.
[0101] The average particle size of the non-magnetic powder is not particularly limited as long as it is 3 μm or less, but is preferably 0.1 to 2.8 μm, and more preferably 0.5 to 2.5 μm. Such a particle size is a particle size necessary for the non-magnetic powder to fill the exudation path of the thermosetting resin, and is a particle size that easily flows together with the molten thermosetting resin.
[0102] The average particle size of the non-magnetic powder may be 3 μm or less and smaller than the average particle size of the magnetic powder, but the difference is preferably 5 μm or more, more preferably 10 to 100 μm, and even more preferably 15 to 60 μm.
[0103] In addition, the sphericity of the non-magnetic particles contained in the non-magnetic powder is not particularly limited, but is preferably 0.50 to 1.00, and more preferably 0.75 to 1.00. By making the sphericity of the non-magnetic powder within the above range, the rolling of the non-magnetic powder itself is utilized to ensure the flowability of the resin composition, while the non-magnetic powder is easily clogged in gaps, etc., making it easier to suppress the exudation of the thermosetting resin. In other words, it is possible to achieve both the flowability of the resin composition and the suppression of the exudation of the thermosetting resin.
[0104] The volume fraction of such non-magnetic powder is preferably 3 to 25 volume % of the magnetic powder, and more preferably 5 to 20 volume %. The volume fraction of the non-magnetic powder is 5 to 10 volume % and preferably 6 to 9.5 volume % relative to 100 mass % of the total solid content of the resin composition. This optimizes the content of the non-magnetic powder, resulting in a resin composition that has sufficient fluidity and can more reliably suppress the exudation of the thermosetting resin.
[0105] By setting the volume fraction of the non-magnetic powder to the lower limit or less, it is possible to suppress the reduction in the effect of improving the fluidity brought about by the non-magnetic powder, the reduction in the fluidity of the resin composition, or the reduction in the effect of suppressing the exudation of the thermosetting resin. Also, by setting the volume fraction of the non-magnetic powder to the upper limit or less, it is possible to suppress the reduction in the magnetic properties and fluidity of the resin composition caused by a relative reduction in the volume fraction of the magnetic powder or the volume fraction of the thermosetting resin.
[0106] On the other hand, the mass fraction of the non-magnetic powder is preferably 1% by mass to 10% by mass, more preferably 2% by mass to 5% by mass, based on 100% by mass of the total solid content of the resin composition, although it varies depending on the specific gravity of each component. This makes it possible to obtain a resin composition that has sufficient fluidity and can more reliably suppress the exudation of the thermosetting resin, as in the case of the volume fraction.
[0107] The average particle size of the iron-based particles, the first particles, the second particles, or the non-magnetic powder means the volume average particle size (e.g., D50), and can be measured using a laser diffraction particle size distribution analyzer. The particle size of the microparticles can be measured using a laser diffraction particle size distribution analyzer.
[0108] The sphericity of particles such as the first particle, the second particle, the microparticle, or the non-magnetic particle can be calculated by dividing the diameter of the equivalent circle by the diameter of the circumscribed circle, assuming that the circle has an area equal to that of the particle in a scanning electron microscope (SEM) image. The diameter of the equivalent circle / the diameter of the circumscribed circle are calculated for 10 or more particles selected arbitrarily, and the average value is taken as the "sphericity of the particle."
[0109] The resin composition of the present embodiment may contain a curing accelerator, which can improve the curability of the resin composition. The curing accelerator may be, for example, any accelerator that accelerates the crosslinking reaction of a thermosetting resin, and may include one or more selected from phosphorus atom-containing compounds such as organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, and adducts of phosphonium compounds and silane compounds; imidazoles such as 2-methylimidazole (imidazole curing accelerators); and nitrogen atom-containing compounds such as amidines and tertiary amines, exemplified by 1,8-diazabicyclo[5.4.0]undecene-7 and benzyldimethylamine, and quaternary salts of the amidines and amines.
[0110] The content of the curing accelerator is, for example, 0.01% by mass to 1% by mass, and preferably 0.05% by mass to 0.8% by mass, relative to 100% by mass of the total solid content of the resin composition. By setting the content within such a numerical range, the curing property can be improved.
[0111] The resin composition of the present embodiment may contain a mold release agent, which can improve the mold releasability of the resin composition during molding. Examples of the release agent include natural waxes such as carnauba wax, synthetic waxes such as montan acid ester wax and oxidized polyethylene wax, higher fatty acids such as zinc stearate and metal salts thereof, and paraffin, etc. These may be used alone or in combination of two or more kinds.
[0112] The content of the release agent is, for example, 0.01% by mass to 3% by mass, and preferably 0.05% by mass to 2% by mass, relative to 100% by mass of the total solid content of the resin composition, which can improve the mold releasability during molding.
[0113] The resin composition of the present embodiment may contain a stress reducing agent, which can suppress the occurrence of cracks and breakage in a cured product of the resin composition and improve brittleness. Examples of the low stress agent include polybutadiene compounds, acrylonitrile butadiene copolymer compounds, silicone oils, silicone rubbers, etc. These may be used alone or in combination of two or more kinds.
[0114] The resin composition of the present embodiment may contain a coupling agent, which can increase the fluidity of the resin composition. As the coupling agent, the coupling agents used in the above-mentioned surface treatment can be used, and examples thereof include silane-based coupling agents, titanium-based coupling agents, zirconia-based coupling agents, and aluminum-based coupling agents.
[0115] (Other Ingredients) The resin composition of the present embodiment may contain components other than the above-mentioned components. Examples of other components include adhesion aids, colorants, antioxidants, anti-corrosive agents, dyes, pigments, and flame retardants.
[0116] The resin composition of the present embodiment can be in a solid state at room temperature of 25° C., and can have a predetermined shape such as powder, granules, or tablets.
[0117] Next, the characteristics of the resin composition of this embodiment will be described.
[0118] The lower limit of the gelation time of the resin composition of this embodiment at 175°C is, for example, 5 seconds or more, preferably 7 seconds or more, and more preferably 10 seconds or more. By making the gelation time equal to or more than the lower limit, moldability can be improved. Specifically, moldability of coils (large structures) such as reactors for vehicles can be improved. On the other hand, the upper limit of the gelation time is, for example, 300 seconds or less, preferably 240 seconds or less, and more preferably 220 seconds or less. By setting the gelation time to the upper limit or less, although the detailed mechanism is unclear, it is considered that uneven distribution of the magnetic powder during molding can be suppressed, so that it is possible to suppress the occurrence of variations in the relative magnetic permeability and improve the magnetic properties. It is also possible to improve the tact time and increase productivity. Therefore, the resin composition of this embodiment can be highly compatible with existing transfer molding processes.
[0119] The melt viscosity of the resin composition of this embodiment at 175°C is, for example, 1 Pa·s or more and 1000 Pa·s or less, preferably 2 Pa·s or more and 800 Pa·s or less, and more preferably 3 Pa·s or more and 500 Pa·s or less. By setting the melt viscosity to the above upper limit or less, it is possible to increase the fluidity and realize excellent moldability. In addition, by setting the melt viscosity to the above lower limit or more, it is possible to suppress the resin leakage from the mold during molding, and to suppress the sedimentation of the magnetic powder in the resin composition during molding. In addition, it is possible to suppress damage to the insulating layer on the particle surface of the magnetic powder and non-magnetic powder.
[0120] The glass transition temperature of the cured product of the resin composition of the present embodiment is, for example, 120° C. or more and 300° C. or less, preferably 125° C. or more and 290° C. or less, and more preferably 130° C. or more and 280° C. or less. By setting the glass transition temperature to the above lower limit or more, the heat resistance can be improved.
[0121] The average linear expansion coefficient α1 of the cured product of the resin composition of this embodiment at room temperature ranging from 25° C. to 70° C. is, for example, 30 ppm / ° C. or less, preferably 28 ppm / ° C. or less, and more preferably 25 ppm / ° C. or less. This can improve the dimensional stability in an environment near room temperature. The lower limit of the average linear expansion coefficient α1 at room temperature ranging from 25° C. to 70° C. is not particularly limited, but may be 1 ppm / ° C. or more.
[0122] The average linear expansion coefficient α2 of the cured product of the resin composition of this embodiment in the range of 270° C. to 290° C. is, for example, 20 ppm / ° C. to 80 ppm / ° C., preferably 22 ppm / ° C. to 75 ppm / ° C., and more preferably 25 ppm / ° C. to 70 ppm / ° C. By setting the average linear expansion coefficient α2 to the above upper limit or less, the dimensional stability in a high-temperature environment can be improved.
[0123] In the cured product of the resin composition of this embodiment, when the length in the longitudinal direction before thermomechanical analysis is taken as a reference length L0 and the amount of thermal expansion from the reference length L0 when the cured product is held at 175°C for 4 hours is taken as L1, the dimensional shrinkage ratio shown by L1 / L0 x 100 is, for example, 1% or less, preferably 0.9% or less, and more preferably 0.8% or less. This can improve heat resistance and dimensional stability. The lower limit of the dimensional shrinkage ratio may be 0% or more.
[0124] The peak temperature of Tan δ obtained by dynamic viscoelasticity measurement at a frequency of 10 Hz of the cured product of the resin composition of this embodiment is, for example, 120° C. to 300° C., preferably 130° C. to 290° C., and more preferably 140° C. to 280° C. By making the peak temperature of Tan δ equal to or higher than the lower limit, it is possible to maintain thermal properties in a high-temperature environment and to increase heat resistance.
[0125] The storage modulus E of the cured product of the resin composition of this embodiment at room temperature (25° C.) 25However, the storage modulus E is, for example, 10 GPa or more and 100 GPa or less, preferably 15 GPa or more and 90 GPa or less, and more preferably 20 GPa or more and 80 GPa or less. 25 By making it equal to or more than the above lower limit, the mechanical strength can be improved.
[0126] The storage modulus E at 150° C. of the cured product of the resin composition of this embodiment 150 is, for example, 1 GPa or more and 100 GPa or less, preferably 3 GPa or more and 90 GPa or less, and more preferably 5 GPa or more and 80 GPa or less. 150 By making the content of the polymerizable composition equal to or greater than the above lower limit, it is possible to realize a cured product that has high strength and excellent shape stability in a high-temperature environment.
[0127] The cured product of the resin composition of this embodiment has a bending strength at room temperature of 25° C. of, for example, 70 MPa to 1000 MPa, preferably 80 MPa to 800 MPa, and more preferably 90 MPa to 500 MPa. By making the bending strength at room temperature of 25° C. equal to or higher than the lower limit, the mechanical strength can be improved.
[0128] The cured product of the resin composition of the present embodiment has a flexural modulus of, for example, 10 GPa to 100 GPa, preferably 12 GPa to 80 GPa, and more preferably 15 GPa to 50 GPa at room temperature 25° C. By making the flexural modulus at room temperature 25° C. equal to or higher than the lower limit, the mechanical strength can be improved.
[0129] The water absorption rate of the cured product of the resin composition of this embodiment when immersed in hot water at 100°C for 24 hours is, for example, 1 wt% or less, preferably 0.8 wt% or less, and more preferably 0.5 wt%. This can increase the water absorption resistance, thereby improving reliability. The lower limit of the water absorption rate is not particularly limited, but may be, for example, 0 wt% or more.
[0130] The difference in linear expansion coefficient between the cured product of the resin composition of this embodiment and copper at room temperature of 25° C. is, for example, 10 ppm / ° C. or less, preferably 9 ppm / ° C. or less, and more preferably 8 ppm / ° C. or less. This makes it possible to reduce the difference in linear expansion coefficient with the copper coil, thereby suppressing the occurrence of cracks and deformation.
[0131] The thermal conductivity of the cured product of the resin composition of this embodiment is, for example, 2 W / m·K or more, preferably 2.5 W / m·K or more, and more preferably 3 W / m·K or more. This allows a cured product with excellent heat dissipation properties to be realized. The upper limit of the thermal conductivity is not particularly limited, but may be, for example, 100 W / m·K or less.
[0132] When an AC magnetic field of 50 mT and 50 kHz is applied to the cured product of the resin composition of this embodiment, the iron loss is, for example, 500 kW / m 3 less than or equal to 300 kW / m 3 More preferably, it is 150 kW / m or less. 3 This makes it possible to realize a cured product with excellent low magnetic loss properties.
[0133] In this embodiment, the above characteristics can be controlled by appropriately selecting, for example, the type and amount of each component contained in the resin composition, the preparation method of the resin composition, etc. Among these, for example, the use of two types of particles having different average particle sizes as the magnetic powder, the surface treatment of the magnetic powder, and the appropriate selection of the content of the curing accelerator are cited as elements for setting the above characteristics within the desired numerical range.
[0134] Next, a method for producing the resin composition of this embodiment will be described.
[0135] The method for producing the resin composition of the present embodiment includes a step of mixing raw material components such as the above-mentioned thermosetting resin and magnetic powder. The magnetic powder may be a mixed powder containing iron-based particles and fine particles. The magnetic powder and the iron-based particles contained therein may be subjected to the above-mentioned surface treatment.
[0136] An example of the surface treatment step can include a step (i) of subjecting the first particles to a plasma treatment, and a step (ii) of reacting the first particles that have been subjected to the plasma treatment in step (i) with a coupling agent.
[0137] (Step (i)) First, the first particles are subjected to plasma treatment. At this time, it is preferable to uniformly perform the plasma treatment on the surfaces of the first particles. This activates the surfaces of the first particles, and allows the coupling agent to react efficiently. To uniformly perform the plasma treatment, for example, the first particles are dispersed in the air and then subjected to the plasma treatment.
[0138] The plasma treatment is preferably an oxygen plasma treatment, which allows the surfaces of the first particles to be efficiently modified with OH groups.
[0139] The pressure of the oxygen plasma treatment is not particularly limited, but is preferably 100 to 200 Pa, and more preferably 120 to 180 Pa.
[0140] The flow rate of the treatment gas in the oxygen plasma treatment is not particularly limited, but is preferably 1000 to 5000 mL / min, and more preferably 2000 to 4000 mL / min.
[0141] The output of the oxygen plasma treatment is not particularly limited, but is preferably 100 to 500 W, and more preferably 200 to 400 W.
[0142] The treatment time for the oxygen plasma treatment is appropriately set depending on the various conditions described above, but is preferably 5 to 60 minutes, and more preferably 10 to 40 minutes.
[0143] Furthermore, an argon plasma treatment may be further performed before the oxygen plasma treatment, which allows active sites for modifying the surfaces of the first particles with OH groups to be formed, thereby enabling the modification with OH groups to be performed more efficiently.
[0144] The pressure of the argon plasma treatment is not particularly limited, but is preferably 10 to 100 Pa, and more preferably 15 to 80 Pa.
[0145] The flow rate of the treatment gas in the argon plasma treatment is not particularly limited, but is preferably 10 to 100 mL / min, and more preferably 20 to 80 mL / min.
[0146] The output of the argon plasma treatment is preferably 100 to 500 W, and more preferably 200 to 400 W.
[0147] The treatment time for the argon plasma treatment is preferably 5 to 60 minutes, and more preferably 10 to 40 minutes.
[0148] (Step (ii)) Next, the first particles immediately after the plasma treatment in step (i) are reacted with the coupling agent. For example, the first particles immediately after the plasma treatment in step (i) are immersed in a dilute solution of the coupling agent, or the coupling agent is directly sprayed onto the first particles. This makes it easier for the reaction to proceed, and makes it easier to modify the surface of the first particles. Here, "immediately after the plasma treatment" refers to a range of 0 to 24 hours after the plasma treatment.
[0149] The amount of the coupling agent used is, for example, preferably 0.05 to 1 part by mass, and more preferably 0.1 to 0.5 parts by mass, relative to 100 parts by mass of the first particles.
[0150] Examples of the solvent used in the reaction with the coupling agent include methanol, ethanol, and isopropyl alcohol.
[0151] The amount of the coupling agent used is preferably 0.1 to 2 parts by mass, and more preferably 0.5 to 1.5 parts by mass, based on 100 parts by mass of the solvent.
[0152] The reaction time with the coupling agent (for example, the time of immersion in a diluted solution) is preferably 1 to 24 hours.
[0153] According to this production method, it is possible to efficiently produce a magnetic powder that can improve the flowability when mixed with a resin composition.
[0154] In this manner, a magnetic powder containing iron-based particles such as the surface-treated first particles and second particles can be prepared.
[0155] Next, the magnetic powder, the thermosetting resin, and other additives as necessary are mixed using a mixer, and then kneaded using a roll, for example, at 120°C for 5 minutes to obtain a kneaded product. The kneaded product obtained is cooled and then pulverized to obtain a powdered resin composition (molding material). The powdered resin composition may then be tableted and compressed into granules or tablets as necessary. This provides a resin composition suitable for transfer molding. In addition, by solidifying the resin composition at room temperature of 25°C, it is possible to improve transportability and storage properties.
[0156] Such a resin composition is molded by various molding methods such as transfer molding, injection molding, extrusion molding, and press molding. As a result, the thermosetting resin melts and flows, and is molded into a desired shape. Among these, the resin composition of the present embodiment can be suitably used for transfer molding.
[0157] The resin composition thus obtained is then cured to obtain a molded product (cured product). Such a molded product can be used as a magnetic core in an inductor such as a reactor.
[0158] An outline of a structure (inductor) having a magnetic core made of a cured product of the resin composition of this embodiment will be described with reference to FIG. Fig. 1(a) shows an overview of the structure 100 as viewed from above. Fig. 1(b) shows a cross-sectional view taken along line AA' in Fig. 1(a).
[0159] The structure 100 of this embodiment can include a coil 10 and a magnetic core 20, as shown in Fig. 1. The magnetic core 20 is filled inside the coil 10, which is an air-core coil. A pair of coils 10 shown in Fig. 1(a) are connected in a parallel state. In this case, the annular magnetic core 20 has a structure that penetrates the inside of the pair of coils 10 shown in Fig. 1(b). The magnetic core 20 and the coil 10 can have an integrated structure. The structure 100 may have a structure in which an insulator (not shown) is interposed between the coil 10 and the magnetic core 20 in order to ensure insulation between them.
[0160] In the structure 100 of this embodiment, the coil 10 and the magnetic core 20 may be sealed with an exterior member 30 (sealing member). For example, the coil 10 and the magnetic core 20 may be housed in a housing (case), liquid resin is introduced therein, and the liquid resin may be cured as necessary to form the exterior member 30 around the coil 10 and the magnetic core 20. In this case, the coil 10 may have an unillustrated lead-out portion in which an end of the winding is led out to the outside of the exterior member 30.
[0161] The coil 10 is usually constructed by winding a metal wire with an insulating coating on its surface. The metal wire is preferably highly conductive, and copper or a copper alloy is preferably used. The insulating coating may be enamel or the like. The cross-sectional shape of the winding may be circular, rectangular, hexagonal, or the like.
[0162] On the other hand, the cross-sectional shape of the magnetic core 20 is not particularly limited, but may be, for example, a circular shape or a polygonal shape such as a square or a hexagon in cross section. The magnetic core 20 is made of a transfer molded product of the resin composition of this embodiment, and therefore can have a desired shape.
[0163] According to the cured product of the resin composition of this embodiment, a magnetic core 20 having excellent magnetic properties such as moldability and high magnetic permeability can be realized, so that low magnetic loss is expected in a structure 100 such as a reactor including this magnetic core 20. In addition, since a magnetic core 20 having excellent mechanical properties can be realized, it is possible to improve the durability, reliability, and manufacturing stability of the structure 100. Therefore, the structure 100 of this embodiment can be used in a reactor for a boost circuit or a large current.
[0164] The present invention has been specifically described above based on the embodiments, but these are merely examples of the present invention, and various configurations other than those described above can also be adopted. Below, examples of reference forms are given. 1. A resin composition for forming a magnetic core, which is used to form a magnetic core filled inside an air-core coil, A thermosetting resin; A magnetic powder; The content of the magnetic powder is 50% by mass or more based on the total solid content of the resin composition for forming a magnetic core, The resin composition for forming a magnetic core has a gelation time at 175°C of 5 seconds or more and 300 seconds or less. 2. The resin composition for forming a magnetic core according to 1., The resin composition for forming a magnetic core has a glass transition temperature of 120°C or higher and 300°C or lower after curing. 3. The resin composition for forming a magnetic core according to 1. or 2., The average linear expansion coefficient α of the cured product of the resin composition for forming a magnetic core at room temperature in the range of 25°C to 70°C 1 The resin composition for forming a magnetic core has a viscosity of 30 ppm / ° C. or less. 4. A resin composition for forming a magnetic core according to any one of 1. to 3., The average linear expansion coefficient α of the cured product of the resin composition for forming a magnetic core in the range of 270°C to 290°C 2 The resin composition for forming a magnetic core, wherein the viscosity is 20 ppm / °C or more and 80 ppm / °C or less. 5. A resin composition for forming a magnetic core according to any one of 1. to 4., The length of the cured product of the resin composition for forming a magnetic core before the thermomechanical analysis is taken as the reference length L 0 The reference length L when the cured product was kept at 175° C. for 4 hours 0 The amount of thermal expansion from L 1 Then, L 1 / L 0 The resin composition for forming a magnetic core has a dimensional shrinkage rate, expressed as x100, of 1% or less. 6. A resin composition for forming a magnetic core according to any one of 1. to 5., The resin composition for forming a magnetic core has a peak temperature of Tan δ, obtained by dynamic viscoelasticity measurement at a frequency of 10 Hz, of 120°C or higher and 300°C or lower, when cured. 7. A resin composition for forming a magnetic core according to any one of 1. to 6., The storage modulus E of the cured product of the resin composition for forming a magnetic core at room temperature (25°C) 25 The resin composition for forming a magnetic core has a compressive strength of 10 GPa or more and 100 GPa or less. 8. A resin composition for forming a magnetic core according to any one of 1. to 7., The resin composition for forming a magnetic core, when cured, has a bending strength of 70 MPa or more and 1000 MPa or less at room temperature (25°C). 9. A resin composition for forming a magnetic core according to any one of 1. to 8., The resin composition for forming a magnetic core has a flexural modulus of elasticity of 10 GPa or more and 100 GPa or less at room temperature (25° C.) when cured. 10. A resin composition for forming a magnetic core according to any one of 1. to 9., A resin composition for forming a magnetic core, the cured product of which has a water absorption rate of 1 wt % or less when immersed in hot water at 100° C. for 24 hours. 11. A resin composition for forming a magnetic core according to any one of 1. to 10., A resin composition for forming a magnetic core, in which the difference in linear expansion coefficient between a cured product of the resin composition for forming a magnetic core and copper at room temperature (25°C) is 10 ppm / °C or less. 12. A resin composition for forming a magnetic core according to any one of 1. to 11., The resin composition for forming a magnetic core, wherein the thermosetting resin comprises an epoxy resin. 13. A resin composition for forming a magnetic core according to any one of 1. to 12., A resin composition for forming a magnetic core, comprising a curing agent for the thermosetting resin. 14. The resin composition for forming a magnetic core according to 13., The resin composition for forming a magnetic core, wherein the curing agent comprises a phenol-based curing agent or an aromatic diamine. 15. A resin composition for forming a magnetic core according to any one of 1. to 14., A resin composition for forming a magnetic core, comprising a release agent. 16. A resin composition for forming a magnetic core according to any one of 1. to 15., The magnetic core-forming resin composition, wherein the magnetic powder contains two types of particles having different average particle sizes. 17. A resin composition for forming a magnetic core according to any one of 1. to 16., A resin composition for forming a magnetic core, the content of the magnetic substance powder being 90 mass % or more based on the total solid content of the resin composition for forming a magnetic core. 18. A resin composition for forming a magnetic core according to any one of 1. to 17., The magnetic core forming resin composition, wherein the magnetic powder contains microparticles having an average particle size of 3 μm or less. 19. The resin composition for forming a magnetic core according to 18., The content of the microparticles in the resin composition for forming a magnetic core is 1% by mass or more and 40% by mass or less based on the total amount of the magnetic powder. 20. A resin composition for forming a magnetic core according to any one of 1. to 19., The magnetic core forming resin composition comprises iron-based particles having an average particle size of more than 3 μm and not more than 180 μm and an iron content of 85 mass % or more. 21. A resin composition for forming a magnetic core according to any one of 1. to 20., The magnetic core forming resin composition, wherein the magnetic powder contains spherical particles. 22. A resin composition for forming a magnetic core according to any one of 1. to 21., A resin composition for forming a magnetic core, comprising a low stress agent. 23. A resin composition for forming a magnetic core according to any one of 1. to 22., A resin composition for forming a magnetic core, comprising a coupling agent. 24. A resin composition for forming a magnetic core according to any one of 1. to 23., A resin composition for forming a magnetic core, used in transfer molding. 25. A structure having a magnetic core made of a cured product of the resin composition for forming a magnetic core described in any one of 1. to 24. EXAMPLES
[0165] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0166] <Preparation of Resin Composition> [Examples 1 to 6] For each of the Examples, a resin composition was prepared as follows. First, the raw material components were mixed in a mixer according to the raw material components and their blending ratios shown in Table 2. The resulting mixture was then roll-kneaded, cooled, pulverized, and tableted to obtain a tablet-shaped resin composition.
[0167] [Comparative Example 1] In Comparative Example 1, the liquid resin components (epoxy resin 3, phenolic resin 2, imidazole-based curing accelerator 2) in Table 2 were mixed with the magnetic powders (iron-based particles 1, iron-based particles 2, microparticles 1) in Table 2 according to the compounding ratio in Table 2 to obtain a resin composition.
[0168] [Comparative Examples 2 and 3] In Comparative Examples 2 and 3, tablet-shaped resin compositions were obtained in the same manner as in Example 1 using the raw material components and their blending ratios shown in Table 2.
[0169] (thermosetting resin) Epoxy resin 1: Epoxy resin (Mitsubishi Chemical Corporation, trisphenylmethane type epoxy resin, E1032H60, solid at room temperature of 25°C) Epoxy resin 2: Epoxy resin (Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, YL6810, solid at room temperature of 25°C) Epoxy resin 3: Epoxy resin (DIC Corporation, bisphenol F type epoxy resin, EPICLON 830-S, liquid at room temperature of 25°C (3000 to 4500 mPa s)) Epoxy resin 4: Epoxy resin containing a biphenylaralkyl structure (manufactured by Nippon Kayaku Co., Ltd., NC3000, solid at 25°C)
[0170] (hardening agent) Phenolic resin 1: Novolac type phenolic resin (Sumitomo Bakelite Co., Ltd., PR-HF-3, solid at room temperature of 25°C) Phenolic resin 2: Novolac type phenolic resin (MEH-8000H, manufactured by Meiwa Kasei Co., Ltd., liquid at room temperature of 25°C (1500 to 3500 mPa s)) Aromatic diamine 1: 2,2'-bis[4-(4-aminophenoxy)phenyl]propane (Seika Corporation, BAPP, solid at 25°C, melting point 128°C) Aromatic diamine 2: 1,3-bis(4-aminophenoxy)benzene (Seika Corporation, TPE-R, solid at 25°C, melting point 116°C)
[0171] (Release agent) Release agent 1: Synthetic wax (Clariant Chemicals, Ester Wax WE-4) (Cure accelerator) Imidazole-based curing accelerator 1: Imidazole-based curing accelerator (Shikoku Chemical Industry Co., Ltd., Curesol 2PZ-PW) Imidazole-based curing accelerator 2: Imidazole-based curing accelerator (Shikoku Chemical Industry Co., Ltd., Curesol 2P4MZ)
[0172] (Magnetic powder) Iron-based particle 1: amorphous magnetic powder (Epson Atmix Corporation, KUAMET6B2, average particle size 50 μm, sphericity 0.85) Iron-based particles 2: Alloy steel powder (DAPMSC5, manufactured by Daido Steel Co., Ltd., average particle size 10 μm, sphericity 0.80) Iron-based particles 3: amorphous magnetic powder (Epson Atmix Corporation, KUAMET6B2 (different sieve size for classification from iron-based particles 1), average particle size 25 μm, sphericity 0.88) Microparticle 1: Carbonyl iron powder (BASF, CIP-HQ, average particle size 2 μm, sphericity 0.90)
[0173] [Table 1]
[0174] The alloy composition of the constituent materials of the magnetic powder shown in Table 2 is as shown in the above Table 1. "Bal." in Table 1 indicates the balance of elements other than Fe.
[0175] (Non-magnetic powder) Non-magnetic particle 1: Silica (SO-25R, manufactured by Admatechs Co., Ltd., average particle size 0.5 μm, sphericity 0.92) Non-magnetic particles 2: Silica (SO-32R, manufactured by Admatechs Co., Ltd., average particle size 1.5 μm, sphericity 0.93)
[0176] [Table 2]
[0177] In Example 1, the content of the magnetic powder is 78% by volume relative to the total solid content of the resin composition, the content of the iron-based particles is 70% by volume relative to the total solid content of the resin composition, and the content of the microparticles is 8% by volume relative to the total solid content of the resin composition. In Example 2, the content of the magnetic powder is 78% by volume relative to the total solid content of the resin composition, the content of the iron-based particles is 55% by volume relative to the total solid content of the resin composition, and the content of the microparticles is 23% by volume relative to the total solid content of the resin composition. In Example 3, the content of the magnetic powder is 78% by volume relative to the total solid content of the resin composition, the content of the iron-based particles is 70% by volume relative to the total solid content of the resin composition, and the content of the non-magnetic powder is 8% by volume relative to the total solid content of the resin composition. In Example 4, the content of the magnetic powder is 78 vol. % relative to the total solid content of the resin composition, and the content of the iron-based particles is 70 vol. % relative to the total solid content of the resin composition. In Example 5, the content of the magnetic powder is 78 vol. % relative to the total solid content of the resin composition, and the content of the iron-based particles is 70 vol. % relative to the total solid content of the resin composition. In Example 6, the content of the magnetic powder is 78 vol. % relative to the total solid content of the resin composition, and the content of the iron-based particles is 65 vol. % relative to the total solid content of the resin composition. In Comparative Example 1, the content of the magnetic powder was 78 volume % based on the total solid content of the resin composition, the content of the iron-based particles was 55 volume % based on the total solid content of the resin composition, and the content of the microparticles was 23 volume % based on the total solid content of the resin composition.
[0178] [Table 3]
[0179] <Evaluation of Resin Composition> The resin compositions obtained in the above Examples and Comparative Examples were evaluated based on the following evaluation items. The evaluation results are shown in Tables 2 and 3. In Table 2, "-" indicates that evaluation was not possible. In Table 3, "-" indicates that measurement was not performed.
[0180] (Gelation time) The gelation time was determined as follows: 3 g of the obtained resin composition was placed on a hot plate set at 175° C., and the time until gelation was measured was taken as the gelation time (seconds). The evaluation results are shown in Table 2.
[0181] The resin composition of Comparative Example 1 was not a liquid paste at room temperature of 25° C. but a solid, and could not be used as a potting material. Therefore, the resin composition of Comparative Example 1 could not be used for casting, and test pieces could not be prepared, so that the various subsequent evaluations could not be performed.
[0182] Furthermore, as a result of further investigation, it was found that in order to use the resin composition of Comparative Example 1 as a potting material (a paste that is liquid at room temperature of 25° C.), the content ratio of magnetic powder must be at least less than 90% by mass. Even when the content ratio of magnetic powder was 79% by mass (corresponding to Example 1 of Patent Document 1), the gelation time exceeded 600 seconds.
[0183] (Moldability) The obtained resin composition was injected and molded using a low pressure transfer molding machine (Kotaki Seiki Co., Ltd. "KTS-30") at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 120 seconds to produce molded products of small structure: 15mm x 4mm x 4mm and large structure: 50mm x 50mm x 10mm. The appearance of the obtained molded products was visually confirmed to determine whether there were any unfilled areas of material based on the following evaluation criteria. The evaluation results are shown in Table 2. <Evaluation criteria for moldability> Three of the above molded articles were produced, and the three molded articles were evaluated for the presence or absence of unfilled material. ○: Three out of three molded products have no material gaps △: One or two of the three molded products have material infill. ×: 3 out of 3 molded products have material not filled
[0184] The resin composition of Comparative Example 3 was not able to be subjected to the various subsequent evaluations due to molding defects.
[0185] (Magnetic properties: relative permeability) The obtained resin composition was injected and molded using a low pressure transfer molding machine (KOTAKISEIKI Co., Ltd., "KTS-30") at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 120 seconds to obtain a cylindrical molded product with a diameter of 16 mmΦ and a height of 32 mm. The obtained molded product was then post-cured at 175°C for 4 hours to prepare a test piece for evaluating relative permeability. The obtained cylindrical molded product was measured for the BH initial magnetization curve in the range of H = 0 to 100 kA / m using a DC / AC magnetization characteristic tester (METRON GIKEN Co., Ltd., "MTR-1488"), and the maximum value of B / H of the BH initial magnetization curve was taken as the relative permeability. The magnetic properties were evaluated based on the following evaluation criteria. The evaluation results are shown in Table 2. <Evaluation criteria for relative permeability> Five test pieces for evaluating the relative magnetic permeability were prepared, and the variation in the relative magnetic permeability of the five test pieces was evaluated. ○: The difference between the maximum and minimum relative permeability values is less than 1.0 △: The difference between the maximum and minimum relative permeability is 1.0 or more and less than 3.0 ×: The difference between the maximum and minimum relative permeability values is 3.0 or more.
[0186] (Melt Viscosity (175℃)) Using a high-performance flow tester (Shimadzu Corporation CFT-500D) equipped with a die with a diameter of 0.5 mm and a length of 10 mm, the obtained resin composition was charged and the minimum viscosity was measured three times under conditions of a measurement temperature of 175°C and a load of 40 kgf, and the average value of these measurements was taken as the melt viscosity (Pa s) at 175°C. The evaluation results are shown in Table 3.
[0187] (Glass transition temperature (Tg), average linear expansion coefficient α1 (25-70℃), average linear expansion coefficient α2 (270-290℃)) The obtained resin composition was injected and molded using a low pressure transfer molding machine (KOTAKISEIKI Co., Ltd., "KTS-30") at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 120 seconds to obtain a molded product of 15mm x 4mm x 4mm. The molded product obtained was then post-cured at 175°C for 4 hours to prepare a test piece. The obtained test piece was then measured for glass transition temperature (°C), average linear expansion coefficient α1 (ppm / °C) at 25-70°C, and average linear expansion coefficient α2 (ppm / °C) at 270-290°C using a thermomechanical analyzer (Seiko Instruments Inc., TMA100) under the conditions of a measurement temperature range of 0°C to 400°C and a heating rate of 5°C / min. The evaluation results are shown in Table 3.
[0188] (Dimensional shrinkage rate) Using the obtained resin composition, a test piece was prepared using a low pressure transfer molding machine ("KTS-30" manufactured by Kotaki Seiki Co., Ltd.) under the conditions of a mold temperature of 175°C, an injection pressure of 9.8MPa, and a curing time of 120 seconds, and the dimensional shrinkage was measured according to JIS K 6911. At this time, the length in the vertical direction before the thermomechanical analysis measurement was taken as the reference length L0, and the amount of thermal expansion from the reference length L0 when the test piece was held at 175°C for 4 hours was taken as L1, and the dimensional shrinkage was taken as L1 / L0 x 100. The evaluation results are shown in Table 3.
[0189] (Tan δ peak temperature, storage modulus (25℃), storage modulus (150℃)) The obtained resin composition was injected and molded using a low pressure transfer molding machine (KOTAKISEIKI Co., Ltd., "KTS-30") at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 120 seconds to obtain a molded product of 50mm x 10mm x 1mm. The molded product obtained was then post-cured at 175°C for 4 hours to prepare a test piece. The obtained test piece was then subjected to dynamic viscoelasticity measurement using a thermomechanical analyzer (Seiko Instruments Inc., DMA100) under the conditions of a measurement temperature range of 0°C to 300°C, a heating rate of 5°C / min, and a frequency of 10Hz to measure the temperature (°C) at the peak value of tan δ, the storage modulus (GPa) at 25°C, and the storage modulus (GPa) at 150°C. The evaluation results are shown in Table 3.
[0190] (Bending strength (25℃)) The obtained resin composition was injection molded using a low pressure transfer molding machine ("KTS-30" manufactured by Kotaki Seiki Co., Ltd.) at a mold temperature of 175°C, injection pressure of 9.8 MPa, and curing time of 120 seconds to obtain a molded product having a width of 10 mm, a thickness of 4 mm, and a length of 80 mm. The obtained molded product was then post-cured at 175°C for 4 hours to prepare a test specimen. The flexural strength (MPa) of the obtained test specimen at 25°C was measured in accordance with JIS K 6911. The evaluation results are shown in Table 3.
[0191] (Flexural modulus (25℃)) The obtained resin composition was injected and molded using a low pressure transfer molding machine (KTS-30 manufactured by Kotaki Seiki Co., Ltd.) at a mold temperature of 175°C, injection pressure of 9.8 MPa, and curing time of 120 seconds to obtain a molded product having a width of 10 mm, a thickness of 4 mm, and a length of 80 mm. The obtained molded product was then post-cured at 175°C for 4 hours to prepare a test specimen. The flexural modulus (GPa) of the obtained test specimen at 25°C was measured in accordance with JIS K 6911. The evaluation results are shown in Table 3.
[0192] (Water absorption rate) The obtained resin composition was injected and molded using a low pressure transfer molding machine (KTS-30 manufactured by Kotaki Seiki Co., Ltd.) at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 120 seconds to obtain a molded product with a diameter of 50 mmΦ and a thickness of 4 mm. The molded product obtained was then post-cured at 175°C for 4 hours to prepare a test piece. The obtained test piece was then boiled at 100°C for 24 hours to measure the water absorption (wt%) calculated by the following formula. The evaluation results are shown in Table 3. Water absorption rate = (weight increase of test piece after boiling treatment / weight of test piece before boiling treatment) x 100
[0193] (Thermal Conductivity) The obtained resin composition was injected and molded using a low pressure transfer molding machine (KTS-30 manufactured by Kotaki Seiki Co., Ltd.) at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 120 seconds to obtain a molded product with a width of 10 mm, thickness of 1 mm, and length of 10 mm. The obtained molded product was then post-cured at 175°C for 4 hours to prepare a test piece. The thermal conductivity (W / mk) in the thickness direction of the obtained test piece was then measured using the laser flash method. The evaluation results are shown in Table 3.
[0194] (Iron loss (50mT, 50kHz)) The obtained resin composition was injection molded using a low pressure transfer molding machine (KOTAKISEIKI CO., LTD., "KTS-30") at a mold temperature of 175°C, injection pressure of 9.8 MPa, and curing time of 120 seconds to obtain a ring-shaped molded product with an outer diameter of 27 mmΦ, an inner diameter of 15 mmΦ, and a thickness of 3 mm. The obtained molded product was then post-cured at 175°C for 4 hours to prepare a ring-shaped test piece. The hysteresis loss Wh (kW / m) of the obtained ring-shaped test piece was measured using a BH curve tracer at an excitation magnetic flux density Bm of 50 mT and a measurement frequency of 50 kHz. 3 ) and eddy current loss We (kW / m 3 ) and calculate the hysteresis loss Wh + eddy current loss We as iron loss (kW / m 3 The evaluation results are shown in Table 3.
[0195] It was found that the resin compositions of Examples 1 to 6 had smaller variations in relative permeability and superior magnetic properties compared to the resin composition of Comparative Example 2. Although the detailed mechanism is unclear, it is believed that in Comparative Example 2, in which the gelation time was too long, settling of the magnetic powder occurred during transfer molding, causing the density of the magnetic powder to become non-uniform (causing uneven distribution), resulting in a deterioration in magnetic properties. It was found that the resin compositions of Examples 1 to 6 have superior moldability in large structures compared to the resin composition of Comparative Example 3. Here, in the evaluation items of moldability, the large structure represents an index for evaluating the moldability in a large magnetic core for sealing a coil of an in-vehicle reactor or the like, and the small structure represents an index for evaluating the moldability in a small sealing member for sealing a semiconductor package. Although the detailed mechanism is unclear, it is considered that in Comparative Example 3, in which the gelation time is too short, the moving distance of the molding material is shortened, resulting in restrictions on the molding size, and as a result, non-filling occurs during the molding process of the large structure. It was also found that the resin compositions of Examples 1 to 6 had the required characteristics for the magnetic core of a reactor (coil), such as mechanical strength, water absorption resistance, characteristics in a high-temperature environment, low magnetic loss, etc. Therefore, it was found that by forming (transfer molding) a magnetic core filled inside an air-core coil using the resin compositions of Examples 1 to 6 (resin compositions for forming a magnetic core) and sealing the coil, a structure (inductor) with excellent manufacturing stability, low magnetic loss, and mechanical strength can be obtained. [Explanation of symbols]
[0196] 100 structures 10 Coil 20 Magnetic Core 30 Exterior materials
Claims
1. A resin composition for forming a magnetic core for forming a magnetic core filled inside an air-core coil, comprising: A powder, granule, or tablet-shaped molding material, A thermosetting resin; A magnetic powder; The content of the magnetic powder is 90% by mass or more based on the total solid content of the resin composition for forming a magnetic core, The resin composition for forming a magnetic core has a gel time at 175° C. of 5 seconds or more and 300 seconds or less.
2. The resin composition for forming a magnetic core according to claim 1, The resin composition for forming a magnetic core has a glass transition temperature of 120°C or higher and 300°C or lower after curing.
3. The resin composition for forming a magnetic core according to claim 1 or 2, The average linear expansion coefficient α of the cured product of the resin composition for forming a magnetic core at room temperature in the range of 25° C. to 70° C. 1 The resin composition for forming a magnetic core, wherein the viscosity is 30 ppm / ° C. or less.
4. The resin composition for forming a magnetic core according to any one of claims 1 to 3, The average linear expansion coefficient α of the cured product of the resin composition for forming a magnetic core in the range of 270° C. to 290° C. 2 The resin composition for forming a magnetic core, wherein the viscosity is 20 ppm / °C or more and 80 ppm / °C or less.
5. The resin composition for forming a magnetic core according to any one of claims 1 to 4, In the cured product of the resin composition for forming a magnetic core, the length in the longitudinal direction before the thermomechanical analysis is measured is defined as a reference length L 0 The reference length L when the cured product was held at 175° C. for 4 hours 0 The amount of thermal expansion from L 1 When this is done, L 1 / L 0 The resin composition for forming a magnetic core has a dimensional shrinkage rate, expressed as x100, of 1% or less.
6. The resin composition for forming a magnetic core according to any one of claims 1 to 5, The resin composition for forming a magnetic core has a peak temperature of Tan δ, obtained by dynamic viscoelasticity measurement at a frequency of 10 Hz, of 120° C. or higher and 300° C. or lower, when cured.
7. The resin composition for forming a magnetic core according to any one of claims 1 to 6, The storage modulus E of the cured product of the resin composition for forming a magnetic core at room temperature (25° C.) 25 The resin composition for forming a magnetic core, wherein the modulus of elasticity is 10 GPa or more and 100 GPa or less.
8. The resin composition for forming a magnetic core according to any one of claims 1 to 7, The resin composition for forming a magnetic core has a bending strength of 70 MPa or more and 1000 MPa or less at room temperature (25° C.) when cured.
9. The resin composition for forming a magnetic core according to any one of claims 1 to 8, The resin composition for forming a magnetic core has a flexural modulus of elasticity of 10 GPa or more and 100 GPa or less at room temperature (25° C.) when cured.
10. The resin composition for forming a magnetic core according to any one of claims 1 to 9, A resin composition for forming a magnetic core, the water absorption rate of a cured product of which when immersed in hot water at 100°C for 24 hours is 1 wt% or less.
11. The resin composition for forming a magnetic core according to any one of claims 1 to 10, A resin composition for forming a magnetic core, in which the difference in linear expansion coefficient between a cured product of the resin composition for forming a magnetic core and copper at room temperature (25°C) is 10 ppm / °C or less.
12. The resin composition for forming a magnetic core according to any one of claims 1 to 11, The resin composition for forming a magnetic core, wherein the thermosetting resin comprises an epoxy resin.
13. The resin composition for forming a magnetic core according to any one of claims 1 to 12, A resin composition for forming a magnetic core, comprising a curing agent for the thermosetting resin.
14. The resin composition for forming a magnetic core according to claim 13, The resin composition for forming a magnetic core, wherein the curing agent comprises a phenol-based curing agent or an aromatic diamine.
15. The resin composition for forming a magnetic core according to any one of claims 1 to 14, A resin composition for forming a magnetic core, comprising a release agent.
16. The resin composition for forming a magnetic core according to any one of claims 1 to 15, The magnetic core forming resin composition, wherein the magnetic powder contains two types of particles having different average particle sizes.
17. The resin composition for forming a magnetic core according to any one of claims 1 to 16, The magnetic core forming resin composition, wherein the magnetic powder contains microparticles having an average particle size of 3 μm or less.
18. The resin composition for forming a magnetic core according to claim 17, The content of the microparticles in the resin composition for forming a magnetic core is 1% by mass or more and 40% by mass or less based on the total amount of the magnetic powder.
19. The resin composition for forming a magnetic core according to any one of claims 1 to 18, The magnetic core forming resin composition comprises iron-based particles having an average particle size of more than 3 μm and not more than 180 μm and an iron content of 85 mass % or more.
20. The resin composition for forming a magnetic core according to any one of claims 1 to 19, The magnetic core forming resin composition, wherein the magnetic powder contains spherical particles.
21. The resin composition for forming a magnetic core according to any one of claims 1 to 20, A resin composition for forming a magnetic core, comprising a low stress agent.
22. The resin composition for forming a magnetic core according to any one of claims 1 to 21, A resin composition for forming a magnetic core, comprising a coupling agent.
23. A structure comprising a magnetic core made of a cured product of the resin composition for forming a magnetic core according to claim 1 .
Citation Information
Patent Citations
Epoxy resin composition, cured product thereof, new epoxy resin, new polyhydroxy compound, and methods for producing them
JP2006096992A
Reactor
JP2014075596A
Epoxy resin molding material, method for producing molded coil and molded coil
JP2014187152A
Phenol aralkyl resin, manufacturing method therefor, epoxy resin, and thermosetting molding material
JP2017105891A
Magnetic-substance powder and production process therefor, magnetic core and production process therefor, and coil component
WO2016204008A1